2009
DOI: 10.1530/rep-08-0120
|View full text |Cite
|
Sign up to set email alerts
|

Donor Sertoli cells transplanted into irradiated rat testes stimulate partial recovery of endogenous spermatogenesis

Abstract: Irradiation of rat testes leads to the failure to support differentiation of the surviving spermatogonia due to damage of the somatic environment. To determine the involvement of Sertoli cells in this somatic damage, we transplanted seminiferous tubule cells from normal immature GFP-transgenic rats into the testes of irradiated rats. The donor Sertoli cells colonized and developed in the host testes. In many seminiferous tubules, the donor Sertoli cells formed abnormal spherical structures in the lumen, but in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 33 publications
5
24
1
2
Order By: Relevance
“…Since Sertoli cells interact most closely with germ cells and display changes in gene expression when germ cells are lost (Cheng & Bardin, 1987; Guitton et al , 2000) they are most likely involved in signaling the loss of germ cells to lead to the induction of the block. A second observation is that transplantation of normal Sertoli cells from young rats to the interstitium of irradiated rat testes stimulates recovery of spermatogonial differentiation in adjacent tubules (Zhang et al , 2009). And the third is our previous observations that FSH enhances the spermatogonial differentiation block (Shetty et al , 2006), which clearly shows that Sertoli cells also have some role in the inhibition of spermatogonial differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Since Sertoli cells interact most closely with germ cells and display changes in gene expression when germ cells are lost (Cheng & Bardin, 1987; Guitton et al , 2000) they are most likely involved in signaling the loss of germ cells to lead to the induction of the block. A second observation is that transplantation of normal Sertoli cells from young rats to the interstitium of irradiated rat testes stimulates recovery of spermatogonial differentiation in adjacent tubules (Zhang et al , 2009). And the third is our previous observations that FSH enhances the spermatogonial differentiation block (Shetty et al , 2006), which clearly shows that Sertoli cells also have some role in the inhibition of spermatogonial differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Reciprocal spermatogonial transplantation experiments have shown functionally that the defect caused by irradiation in the rat testes that results in the block of spermatogonial differentiation must be due to injury to the somatic compartment, not the germ cells (Zhang et al 2007). Furthermore, they have also shown that the transplantation of Sertoli cells from normal immature rats into the interstitium of testes of irradiated rats stimulates partial recovery of endogenous spermatogenesis (Zhang et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Иccлeдoвaниe пaтoмopфoлoгoв пoзвoлили уcтaнoвить, чтo клeтки, утpaчивaя cвязь c cуcтeнтoцитaми, пoдвepгaютcя лизиcу ядepнoгo aппapaтa [49]. В изучeннoй нaми литepaтуpe былa нaйдeнa paбoтa, coглacнo кoтopoй нa мecтe пoгибших cпepмaтoцитoв в эпитeлии кaнaльцeв нepeдкo вoзникaют пoлocти oкpуглoй фopмы.…”
Section: Peзультaты исследования и их Oбcуждeниeunclassified
“…Aнaлиз литepaтуpы, пpoвeдeнный в дaннoй paбoтe, cвидeтeльcтвуeт o том, чтo пocлe вoздeйcтвия γ-излучeния в дoзaх пo-pядкa 1,0-3,0 Гp диффepeнциaция cпep-мaтoгoний пoлнocтью пpeкpaщaeтcя. Cлe-дoвaтeльнo, иcтoщeниe cпepмaтoгoний в пocлeдующeм зaкoнoмepнo oтpaжaeтcя в cнижeнии пpoдукции cпepмaтoзoидoв [49]. При вoздeйcтвии cублeтaльнoй дoзы γ-излучeния уцeлeвшиe cпepмaтoгoнии, пpeдcтaвляющиe coбoй диплoидныe клeтки c oтнocитeльнo бoльшим кoличecтвoм цитoплaзмы, eщё нe утpaчeннoй в пpo-цecce дaльнeйшeгo пpeoбpaзoвaния гa-мeт, oблaдaют выcoкoй cпocoбнocтью к peпapaции пoвpeждeний, пoлучeнных в peзультaтe oблучeния и, кaк извecтнo из литepaтуpных иcтoчникoв, пepeдaют дaльнeйшим пoкoлeниям пoлoвых клeтoк мeньшe пoвpeждeний, чeм пoлучили caми.…”
Section: Peзультaты исследования и их Oбcуждeниeunclassified